Sofia Making Her Mark: Bridging the Cultural Divide - Tamara L. Jacobson (ELITE Association Indonesia, 2021)
The narrative focuses on the importance of Cultural Capital in the Classroom through the experiences of Sofia, a Hispanic, trilingual, engineering student at Columbia University. Through her experiences, I highlight the importance of combining cultures and viewing diversity as a source of knowledge. Sofía’s narrative helps instructors understand the most critical aspects of culturally responsive teaching.